Text as Father : Paternal Seductions in Early Mahayana Buddhist Literature - Cole, Alan, 1964- (Book collections on Project MUSE., 2005)
Alan Cole sheds new light on the origin & nature of Mahāyāna Buddhism with close readings of four well-known texts: the Lotus Sūtra, Diamond Sūtra, Tathāgatagarbha Sūtra, & Vimalakīrtinirdeśa.